Chemical process safety education in China: An overview and the way forward. (April 2022) - Motalifu, Mailidan; Tian, Yue; Liu, Yi; Zhao, Dongfeng; Bai, Mingqi; Kan, Yufeng; Qi, Meng; Reniers, Genserik; Roy, Nitin
Highlights: Professional accreditation of undergraduate Chemical Engineering and Safety Engineering majors in higher education institutions in China. Chemical process safety education through different majors. The current discipline construction of the newly established major Chemical Safety Engineering in China. Suggestions to further promote chemical process safety education. Abstract: The chemical process industry (CPI) in China is developing rapidly with installations becoming more complicated and integrated to meet people's rising demands for chemical-related products. However, the fast-growing CPI has caused catastrophic consequences and bad social influence due to accidents occurred in the last decades, which has threatened its sustainable development. As one of the solutions, the Chinese government is promoting chemical process safety education to train interdisciplinary graduates who understand both chemical process and loss prevention, who are skilled in technology, and how to manage risk. In this paper, we reviewed the development of chemical process safety education in China by researching syllabuses of accredited undergraduate Chemical Engineering and Safety Engineering majors in higher education institutions, discussed the associated shortcomings by analyzing the current discipline construction of the newly established major Chemical Safety Engineering, including education methodologies, resources, faculties, curriculum provision, and professional accreditation. Based on the analysis results, suggestions were provided to encourage institutions to strengthen chemical process safety education, thereby inherently reducing human errors and consequently improving the safety of the entire CPI.